Integration of livelihood support with MHPSS in rehabilitation of torture survivors in LMICs: Addressing poverty and mental health dynamics - Ayesha Mushtaq (Torture)
Introduction: The integration of livelihood support with mental health and psycho-social support (MHPSS) seems crucial for the rehabilitation of torture survivors in low- and middle-income countries (LMICs). This study aimed to explore the intersec-tionality of poverty and mental health, and the integration of livelihood support with-in MHPSS frameworks related to the rehabilitation of torture survivors in LMICs. Method : A cross-sectional study was conducted using a semi-structured questionnaire distributed to members of the International Rehabilitation Council for Torture Victims (IRCT) in LMICs (n=25). The questionnaire explored the perception of IRCT centres in LMIC countries regard-ing the extent to which poverty contributes to poor mental health outcomes among torture sur-vivors and the effectiveness of integrating livelihood support into MHPSS interventions. Results: The study highlighted the significant economic challenges faced by torture survivors, indicating a high prevalence of extreme poverty among this group. The study found that 92% of respondents believed that poverty and mental health outcomes of torture survivors are strongly linked. Eco-nomic and social inequalities were identified as key determinants of mental health, emphasizing the need to address these inequalities in rehabilitation programs for torture survivors. Discussion:The study underscores the critical connection between poverty, mental health, and the experience of torture. In the view of most IRCT centres, the integration of livelihood support with MHPSS is essential for addressing economic disparities and promoting long-term resilience among survivors. The results highlight the need to conduct long-term longitudinal studies that provide support to this perception. The study recommends enhancing coordination among stakeholders, addressing cultural and social barriers, securing sustainable funding, and developing strategies to integrate livelihood support with MHPSS for torture survivors. According to participants, rehabilitation programmes should include economic empowerment, mental health support, and social integration, to contribute to a holistic recovery, long-term resilience, and overall well-being.